Singapore a developmental city state - Perry, Martin (World cities series, 1997)
Singapore has achieved global prominence as the link between the international economy and one of the world's fastest growing regions. This book offers a comprehensive introduction to the city. It reviews the city's social, physical and political characteristics and explores such current dilemmas as the means of accommodating the aspirations of an increasingly affluent population while overcoming the physical constraints of a small island state.